Strengthening Human Resources Through Introduction and Stunting Prevention - Zulkifli Siregar; Nur M Ridha Tarigan; M. Sahnan (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to find solutions to strengthening human resources through the introduction and prevention of stunting. Stunting will cause long-term impacts, namely disruption of physical, mental, intellectual, and cognitive development. Children who are stunted until the age of 5 years will be difficult to repair so that it will continue into adulthood and can increase the risk of offspring with low birth weight (LBW). Strengthening human resources starts at an early age starting from the childhood phase to the adolescent/adult phase. This study uses a qualitative method with a library research model approach, this approach uses theory and expert opinion as the main object of research. Stunting prevention must be the responsibility of each party and related stakeholder to reduce the stunting rate which is still high in Indonesia. Prevention is carried out by campaigning for the anti-stunting movement and providing training to mothers related to stunting. Significant strengthening of human resources will be obtained through suppressing the number of stunting cases and good handling of stunting cases in Indonesia.